IMPLEMENTATION OF THE MEANINGFUL RECEPTION LEARNING APPROACH IN MOTION AND SONG LEARNING - Setiorini Rahma Safitri (JURNAL PAKARENA, 2022)
This research is motivated by the implementation of the Meaningful Reception Learning approach in motion and song learning, which is seen as the most appropriate approach for students at PAUD Jelita. This approach is generally understood as the correlation of children's cognitive schemes to the new material given, resulting in a meaningful learning activity. However, on a practical level how it is implemented, so far no research has studied it. Based on the problems studied, namely regarding the implementation of the Meaningful Reception Learning approach in motion and song learning at PAUD Jelita, Pringsurat Village, Temanggung Regency, this research will use qualitative methods.  The activities carried out include data collection, data verification, analysis, and synthesis. The Meaningful Reception Learning approach in PAUD Jelita Pringsurat, Temanggung, is implemented in large class students whose students are 6 years old. The approach is appropriate when applied in large classes because students are more easily conditioned. The stages of the Meaningful Reception Learning approach can be passed effectively in large-class students. The stages passed are the initial settings (Advance Organizer). The initial arrangement is a classroom conditioning activity carried out by the teacher. Then the second is progressive differentiation, that is, learning from the general thing to the particular. Next is superordinate learning which is concept learning by relating concepts that have been previously understood. In the last stage, it is an integrative adjustment. The stages are carried out in the form of compiling material consisting of various concepts, in which the concepts have a general to a special relationship.